Morphogenetic and histogenetic roles of the temporal-spatial organization of cell proliferation in the vertebrate corticogenesis as revealed by inter-specific analyses of the optic tectum cortex development - Rapacioli, Melina (2016)
The central nervous system areas displaying the highest structural and functional complexity correspond to the so called cortices, i.e. concentric alternating neuronal and fibrous layers. Corticogenesis, i.e. the development of the cortical organization, depends on the temporal-spatial organization of several developmental events: (a) the duration of the proliferative phase of the neuroepithelium, (b) the relative duration of symmetric (expansive) versus asymmetric (neuronogenic) sub phases, (c) the spatial organization of each kind of cell division, (e) the time of determination and cell cycle exit and (f) the time of onset of the post-mitotic neuronal migration and (g) the time of onset of the neuronal structural and functional differentiation. The first five events depend on molecular mechanisms that perform a fine tuning of the proliferative activity. Changes in any of them significantly influence the cortical size or volume (tangential expansion and radial thickness), morphology, architecture and also impact on neuritogenesis and synaptogenesis affecting the cortical wiring. This paper integrates information, obtained in several species, on the developmental roles of cell proliferation in the development of the optic tectum (OT) cortex, a multilayered associative area of the dorsal (alar) midbrain. The present review (1) compiles relevant information on the temporal and spatial organization of cell proliferation in different species (fish, amphibians, birds, and mammals), (2) revises the main molecular events involved in the isthmic organizer (IsO) determination and localization, (3) describes how the patterning installed by IsO is translated into spatially organized neural stem cell proliferation (i.e. by means of growth factors, receptors, transcription factors, signaling pathways, etc.) and (4) describes the morpho- and histogenetic effect of a spatially organized cell proliferation in the above mentioned species. A brief section on the OT evolution is also included. This section considers how the differential operation of cell proliferation could explain differences among species.